Negative Anthropology - Stephan Trüby (Footprint)
Is there an architectural and urban planning agenda at work behind the politics of contemporary (neo-)fascists and populist, radical and extremist right-wing forces? The Right-Wing Spaces research project, which has been running since 2018 at the Institute for Principles of Modern Architecture (Design and Theory) (IGmA) at the University of Stuttgart, suggests that the answer to this question is fairly unequivocal, at least in the German context: ‘architecture … seems to have become a key tool of an authoritarian, populist right with a revisionist take on history.’[i] The interim findings of the project were presented in ‘Rechte Räume: Bericht einer Europareise’ (Right-wing spaces: report on a journey through Europe), ARCH+ 235 (2019), an issue that was guest-curated by IGmA, as well as in my 2020 essay collection Rechte Räume: Politische Essays und Gespräche (Right-wing spaces: political essays and conversations).